Exoplanet transits observed at UNI's Astronomical Observatory - Pereyra, Antonio (2019)
This work present the exoplanet transit program developed at OAUNI on the 2016 and 2017 campaigns. Seventeen exoplanet transits were observed and in six of them more than one event was registered. In a couple of cases the same transit were gathered four times. Preliminary reductions are shown in three transits (WASP-80 b, WASP-52 b, and WASP-77 A b). The associated light curves show well-defined events and their modeling let to infer physical parameters of each system. These measurements are the first ones of their kind collected by a peruvian astronomical facility.